2016
DOI: 10.3892/mmr.2016.4892
|View full text |Cite
|
Sign up to set email alerts
|

Decreased miR-143 and increased miR-21 placental expression levels are associated with macrosomia

Abstract: Abstract. Macrosomia, a birth weight ≥4,000 g, is associated with maternal and infant health problems. The dysregulation of microRNAs (miRNAs) in the placenta is associated with adverse birth outcomes, yet whether aberrantly expressed placental miRNAs are associated with macrosomia remains unknown. The aim of the current study was to characterize the expression of three placental miRNAs (miR-6, -21 and -143) and evaluate their association with macrosomia. The miRNA expression in placental tissues from 67 macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 49 publications
1
23
0
1
Order By: Relevance
“…Two independent studies confirmed increased expression of miR-21 in placenta tissue of infants born with macrosomia (birth weight > 4000 g) [99,100]. Milk miR-21, a signature miR of commercial dairy milk and cargo of bovine milk exosomes [71,72,80], most likely reaches the placenta and increases placental and trophoblast growth.…”
Section: Fetal Macrosomiamentioning
confidence: 83%
“…Two independent studies confirmed increased expression of miR-21 in placenta tissue of infants born with macrosomia (birth weight > 4000 g) [99,100]. Milk miR-21, a signature miR of commercial dairy milk and cargo of bovine milk exosomes [71,72,80], most likely reaches the placenta and increases placental and trophoblast growth.…”
Section: Fetal Macrosomiamentioning
confidence: 83%
“…Downregulation of miR‐143 mediated the metabolic transition from oxidative phosphorylation to aerobic glycolysis in GDM placentas, whereas overexpression of miR‐143 increased mitochondrial respiration and mitochondrial complex expression, and decreased the expression of glycolytic enzymes 52 . Furthermore, miR‐143 might play a role in the mitogen‐activated protein kinase signaling pathway associated with macrosomia 53 . The expression level of miR‐518d in GDM placentas was significantly higher, and high expression of miR‐518d was negatively correlated with peroxisome proliferator‐activated receptor‐α, which might participate in the occurrence of GDM by regulating expression 54 .…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the relationship between placental-specific miRNAs and pregnancy outcomes, researchers compared the expression of miRNAs isolated from the placentas between patients affected by the disorders and healthy controls [ 8 , 51 , 54 , 56 58 ]. Since placental tissues are obtained at the time of delivery, it is unclear whether the aberrant miRNA expression is the cause or the consequence of the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…The suitable approach, mostly used, was to identify disease-related differences in miRNA expression by miRNA microarray or second-generation sequencing in small subgroups, followed by the validation by qRT-PCR on a larger sample size [ 8 , 9 , 13 , 14 , 16 , 23 25 , 31 , 34 , 53 , 58 ]. However, other studies just used qRT-PCR techniques to validate candidate biomarkers identified through literature search or based on previous findings [ 10 , 11 , 18 , 26 , 51 , 52 , 54 , 55 , 57 ]. In addition, variability between studies was also observed in data reporting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation